2012
DOI: 10.1088/0031-9155/57/13/4245
|View full text |Cite
|
Sign up to set email alerts
|

MREIT experiments with 200 µA injected currents: a feasibility study using two reconstruction algorithms, SMM and harmonicBZ

Abstract: Magnetic resonance electrical impedance tomography (MREIT) is a technique that produces images of conductivity in tissues and phantoms. In this technique electrical currents are applied to an object and the resulting magnetic flux density is measured using magnetic resonance imaging (MRI) and the conductivity distribution is reconstructed using these MRI data. Currently the technique is used in research environments, primarily studying phantoms and animals. In order to translate MREIT to clinical applications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
2
3
0
Order By: Relevance
“…Results showed that the J-substitution algorithm consistently gave us better results than the harmonic B z algorithm with the same electrode configuration and noise level, which is consistent with the results published by other groups (Arpinar et al , 2012 and Eyüboğlu et al , 2010). The reason for this phenomenon is that the second-order differentiation of B z is required in the harmonic B z algorithm, while only a first-order differentiation is required in the J-substitution algorithm.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results showed that the J-substitution algorithm consistently gave us better results than the harmonic B z algorithm with the same electrode configuration and noise level, which is consistent with the results published by other groups (Arpinar et al , 2012 and Eyüboğlu et al , 2010). The reason for this phenomenon is that the second-order differentiation of B z is required in the harmonic B z algorithm, while only a first-order differentiation is required in the J-substitution algorithm.…”
Section: Conclusion and Discussionsupporting
confidence: 90%
“…However, three components of magnetic flux density are needed in the J-substitution algorithm and the requirement of 3D rotating the subject in the MRI scanner makes this less practical. Since the sensitivity matrix method (SMM) is more robust to noise (Arpinar et al 2012) and only one component of magnetic flux density measurement is needed to reconstruct the conductivity distribution, this method is more practical in the future clinical application.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, in T2-weighted images, the mean of tissue image intensity is significantly increased in the electrical current group. This result supports the theory of MREIT that can increase the signal intensity of MR images and its quality [31]. This inconsistent result is a subject for further study.…”
Section: Image Intensity Data Of Phantom After Applying Electrical Cu...supporting
confidence: 71%
“…Because only one component of magnetic flux density, B z , the component along the longitudinal axis of an MRI system, can be measured conveniently, specialized techniques have been developed to recover conductivity information from these data [1]. These magnetic resonance electrical impedance tomography (MREIT) approaches have included J-substitution [4], sensitivity-based methods [5], and the Harmonic B z method [6,7]. More recently, additional information provided from diffusion tensor (DT) images have been combined with B z measurements to allow in vivo imaging of conductivity tensors in the human brain [8].…”
Section: Introductionmentioning
confidence: 99%